DLTS investigation of acceptor states in P3MeT Schottky barrier diodes - Jones, G. W. (2015)
Deep Level Transient Spectroscopy (DLTS) has been used to investigate hole traps in the depletion region of Schottky barrier diodes formed from electropolymerised poly(3-methylthiophene). The capacitance transients appear to be composed of a fast and a slow component. Analysis of the slower component using the ''rate window'' technique yields isochronal differential capacitance curves that depend on temperature in the manner predicted by theory.